THE IMPACT OF VOCABULARY LEARNING STRATEGIES ON SPEAKING SKILLS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Vocabulary knowledge plays a crucial role in the development of speaking skills in second language acquisition. Learners with limited vocabulary often struggle to express ideas fluently and accurately, which negatively affects their communicative competence. This article explores the impact of vocabulary learning strategies on learners’ speaking skills, particularly in English as a Second Language (ESL) contexts. It examines how different strategies—such as memorization techniques, contextual learning, semantic mapping, and communicative practice—contribute to oral proficiency. The study highlights the relationship between strategic vocabulary learning and improvements in fluency, accuracy, confidence, and lexical richness in spoken language. By reviewing existing literature and analyzing empirical data, the article demonstrates that learners who actively employ effective vocabulary learning strategies tend to perform better in speaking tasks. Furthermore, the findings suggest